2019
DOI: 10.3390/antiox8120585
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Target Genes Involved in the Effect of Quercetin on the Response to Oxidative Stress in Caenorhabditis elegans

Abstract: Quercetin is one the most abundant flavonoids in the human diet. Although it is well known that quercetin exhibits a range of biological activities, the mechanisms behind these activities remain unresolved. The aim of this work is to progress in the knowledge of the molecular mechanisms involved in the biological effects of quercetin using Caenorhabditis elegans as a model organism. With this aim, the nematode has been used to explore the ability of this flavonoid to modulate the insulin/insulin-like growth fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 45 publications
5
36
0
Order By: Relevance
“…These activities are attributed to the presence of several polyphenols, among them quercetin and myricetin glucosides. Our results are in agreement with a study by Durán et al [25], where the authors reported that quercetin exhibits antioxidant activities in C. elegans that are DAF-16-independent. Additionally, another study by Büchter et al revealed that myricetin exhibits antioxidant activities through nuclear translocation of DAF-16 [26].…”
Section: Discussionsupporting
confidence: 94%
“…These activities are attributed to the presence of several polyphenols, among them quercetin and myricetin glucosides. Our results are in agreement with a study by Durán et al [25], where the authors reported that quercetin exhibits antioxidant activities in C. elegans that are DAF-16-independent. Additionally, another study by Büchter et al revealed that myricetin exhibits antioxidant activities through nuclear translocation of DAF-16 [26].…”
Section: Discussionsupporting
confidence: 94%
“…Mulberry leaf flavonoids have shown to increase the nutrient digestibility, dietary metabolizable energy, and rumen fermentation in pre and post-weaning calves (70,90). The desirable effects of MLF on lactation performance observed in the present study may be attributed to the increased secretion of metabolic hormones and modulation of the insulin/IGF-1 signaling pathway (91).…”
Section: Milk Yield and Compositionmentioning
confidence: 71%
“…Oxidative stress can also be induced by submitting C. elegans to a temperature of 32–37 °C [ 57 ]. The application of a thermal stress has also been commonly used to assess the antioxidant potential of polyphenols in C. elegans [ 21 , 22 , 58 , 59 , 60 , 61 , 62 ].…”
Section: Methodological Approaches For Antioxidants Evaluation In mentioning
confidence: 99%
“…The evolutionary conserved insulin/insulin like growth factor-1 (IGF-1) signaling pathway controls many important biological processes, such as ageing, metabolism or stress resistance throughout species [ 19 , 20 ]. This pathway has been repeatedly proposed as a key target in the biological effects of different polyphenols [ 21 , 22 , 23 , 24 , 25 ]. Also, the activation of mitogen-activated protein kinases (MAPK) and subsequent inhibition of the mammalian target of rapamycin (mTOR) signaling pathway has been indicated as a mechanism by which polyphenols might influence energy homeostasis and inflammatory processes [ 13 ].…”
Section: Polyphenols and Oxidative Stressmentioning
confidence: 99%